Lap Joint Dissimilar Welding of Aluminium AA6061 and Galvanized Iron Using TIG Welding - L. H., Shah; U. K., Mohamad; K. I., Yaakob; A. R., Razali; M., Ishak (Faculty Mechanical Engineering, UMP, 2016)
In this paper, aluminium AA6061-O and galvanized iron were lap-joined using tungsten inert gas (TIG) welding. The experiments were conducted using Si-rich filler metals ER4043 (Si 5 wt.%) and ER4047 (Si 12 wt.%). The mechanical properties and the microstructure of the samples were analysed using dye penetrant non-destructive tests (NDT), optical microscope observation and shear tests. All samples showed good quality joints, with Al-GI specimens showing better quality. Through optical microscope observation, the intermetallic compounds (IMC) of specimens using ER4043 fillers show a thin IMC layer ranging from 4 µm to 7 µm, compared to ER4047 samples which ranged between 20 µm and 40 µm. The shear tests show that the GI-Al group fractured at the IMC layer, while the Al-GI group fractured at the FZ-HAZ aluminium matrix. The highest shear strength value obtained was 89.82 MPa and 76.59 MPa for the Al-GI and GI-Al positions, respectively. It can be concluded that the GI-Al (galvanized iron on top and aluminium at the bottom) configuration with filler type ER4043 (Si 5 wt.%) has the optimum mechanical properties with a thin IMC layer and tensile strength of 76.59 MPa.